Design of Student Worksheet Based On Discovery Learning to Improve the Ability of Mathematics Reasoning Students of Class VII Junior High School. (August 2019) - Marian, F; Suparman,
Abstract: The reasoning is one of the important aspects that must be mastered by students in learning mathematics in the 4.0 industrial revolution. The low mathematical reasoning abilities of students will have an impact on the difficulties of students in achieving learning goals and learning outcomes of mathematics. This article aims to design student worksheets based on discovery learning models to optimize students' mathematical reasoning. This research is development research using submodel of ADDIE development (Analysis, Design, Development, Implementation, and Evaluation). The submodel development procedure consists of two stages: analysis and design. The subjects of this study were seventh-grade junior high school students. The object of this research includes curriculum, student characteristics, evaluation of teaching materials. The instruments of data collection in this study were essayed items and interview guidelines. The data analysis technique used in this study is qualitative data analysis. The results of the study are a) at the analysis stage it is known that the learning process is still not meaningful, the learning method used by the teacher has not been able to facilitate students to reason, the student worksheet used does not yet cover all competency indicators in the school. b) the results of the student worksheet design consist of: cover, preface, table of contents, core competencies, basic competencies, indicators of achievement of competencies, material, practice questions based on discovery learning, and problem training. This research can be extended to the stages of development, implementation, and evaluation to produce valid, practical and effective student worksheets.